Pelatihan Penggunaan Aplikasi Penjualan Hewan Ternak Yg Ada Di Kampung Kunyit Desa Tumpatan Nibung Untuk Peningkatan Pendapatan Ekonomi - Nurahmadi, Fauzan; Sihombing, Poltak (Cattleya Darmaya Fortuna, 2024)
This article aims to delve into the impact of training on the utilization of livestock sales applications on the local economy of Kampung Kunyit. The significance of incorporating technology into livestock marketing not only broadens perspectives but also enhances the skills and knowledge of the local community. This article discusses effective and applicable training methods. The piece explores the effective integration of technological advancements, specifically the utilization of a livestock sales application, as a catalyst for economic empowerment. Through a detailed examination, the training methods outlined in the article not only aim to increase digital literacy but also foster a deeper connection between the community and the evolving landscape of agricultural commerce. By steering away from commonplace language, the author successfully communicates complex concepts with precision, ensuring that the content resonates with a diverse audience. The narrative weaves through the challenges faced by rural communities in adapting to technological shifts, providing insights into the innovative strategies employed during the training sessions.